Managing Food Price Risks and Instability in an Environment of Market Liberalization - World Bank (Washington, DC, 2012)
This report, Managing Food Price Risks and Instability in an Environment of Market Liberalization, studies the food price instability and risk problem in low-income countries and investigates the benefits and costs of alternative policy responses, and provides guidance on how to make the transition from state-dominated markets to private markets. The report concludes that problems of food price instability and food insecurity need to be addressed by developing: measures to improve overall productivity of food staples, measures to promote irrigation or crop diversification to reduce climate risks, improvements of the overall efficiency of markets, including investments in transport and communication infrastructure, storage, information systems, and market regulations. The report stresses that direct public interventions in food markets to manage food price risk should be a last resort. Specific policy recommendations are made to achieve these objectives.